A system dynamics-based model to implement the Theory of Constraints in a healthcare system. (July 2019) - Grida, Mohamed; Zeid, Mahmoud
The management of costly and limited healthcare resources, such as operating rooms, doctors, nurses, and beds, is challenged by the uncertainty of arrivals and the service time of different types of patients. Therefore, healthcare units encounter unbalanced utilization of such resources and unnecessary long patient waiting times. A system dynamics model simulating a typical medium-sized hospital, where different types of patients are served using the same limited resources, is developed to implement the Theory of Constraints philosophy. The AnyLogic environment is used for execution. The model is used to identify the system bottleneck resource, then to exploit and to subordinate the system around this resource. The number of served patients (throughput) is increased by 6% without any resource elevation. Furthermore, the model is used to determine the proper capacity needed to elevate the bottleneck resource.